2017
DOI: 10.1016/j.conb.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic strategies to access activated neurons

Abstract: A major goal of modern neuroscience is to understand how ensembles of neurons participate in neural circuits underlying behavior. The recent explosion of genetically-encoded circuit analysis tools has allowed neuroscientists to characterize molecularly-defined neuronal types with unprecedented detail. However, since neurons defined by molecular expression can be functionally heterogeneous, targeting circuit analysis tools to neurons based on their activity is critical to elucidating the neural basis of behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 70 publications
1
91
0
Order By: Relevance
“…The questions about the ongoing reorganization and recruitment of neurons into the LTM engram is indeed highly debated 45,46 . In recent years, the combination of transgenics and optogenetics has allowed neuroscientists to identify memory engram cells by detecting and tagging specific populations of cells that are active during different learning phases 5 . In agreement with our results, one recent study found an activation of neurons in the prelimbic cortex during the retrieval of fear memory in mice in addition to those neurons active during stimulus presentation or early memory recalls 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questions about the ongoing reorganization and recruitment of neurons into the LTM engram is indeed highly debated 45,46 . In recent years, the combination of transgenics and optogenetics has allowed neuroscientists to identify memory engram cells by detecting and tagging specific populations of cells that are active during different learning phases 5 . In agreement with our results, one recent study found an activation of neurons in the prelimbic cortex during the retrieval of fear memory in mice in addition to those neurons active during stimulus presentation or early memory recalls 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic approaches, including immediate early gene-based strategies to tag cells in an activity-dependent manner, have clearly advanced our understanding how neural activity underlies behaviour 5 . However, many of the current methods require fixed tissue to visualize previously active neurons and are therefore inadequate to follow fast temporal dynamics of activity patterns.…”
mentioning
confidence: 99%
“…Genetic access of activated neurons has emerged as an important tool to dissect neural circuit function (40). Using TRAP2 (25), we show that the physiological imbalance following water deprivation produces a motivational drive encoded in the activity of a molecularly defined neuronal type within hypothalamic MnPO.…”
mentioning
confidence: 99%
“…In the last decade, groundbreaking technological advances have allowed neuroscientists to take control of neural firing with impressive precision and specificity ( Figure 1) (4 -7). An in-depth description of these tools is outside the scope of this paper [see (4)(5)(6)(7)(8) for comprehensive descriptions]. Concisely, two techniques have fundamentally changed the landscape of neural circuit dissection: optogenetics, which controls neuronal firing with light, and chemogenetics, which alters neuronal firing with otherwise biologically inert compounds.…”
Section: The Era Of Circuit Mappingmentioning
confidence: 99%